Socioeconomic, work and health characteristics of nutritionists from municipal hospitals in Rio de Janeiro - Barbosa de Aguiar, Odaleia; Muzy da Silva, Tânia (O Mundo da Saúde, 2017)
A historical analysis of the characteristics of nutritionists inserted in the labor market shows greater insertion in the areas of clinical and collective power; loss of wages in recent decades and few studies about the profile and health professional. This research aims to describe the socioeconomic, work. and health characteristics of nutritionists’ statutory staff and CLT employees, from municipal public hospitals of Rio de Janeiro. A cross sectional study was performed with 289 nutritionists, from October 2011 to August 2012 in 23 hospitals. A structured questionnaire was used to access: socioeconomic and employment status, lifestyle habits, and health. Weight, height and waist circumference were measured. It was observed that the variables of age, per capita family income, education, color, years of work as a nutritionist and binge-eating episodes showed significant differences (p <0.05). Statutorily regulated group wasthe largest age group (79.2%), with higher per capita family income (80.7%), with higher degrees “broad and strict sense” (75.7%), and 79.4% reported ≥21 years of work. Among the study population, 47.6% were overweight, 72.5% were sedentary, and 41.9% had binge-eating episodes. Work-related musculoskeletal disorders (MSDs), hypertension, diabetes, hypercholesterolemia and gastritis were more prevalent in the statutorily regulated group (66.7%). As a result of the differences found between the statutorily regulated staff and CLT employees, new studies that support the analysis of the work processes of nutritionists can contribute to the knowledge of the work and health conditions of these workers.